2005
DOI: 10.1016/j.brainres.2005.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Methanesulfonyl fluoride, an acetylcholinesterase inhibitor, attenuates simple learning and memory deficits in ischemic rats

Abstract: Methanesulfonyl fluoride (MSF), a highly selective CNS inhibitor of acetylcholinesterase, has been recently demonstrated to promote improvement in cognitive performance in patients with senile dementia of Alzheimer type. Because a similar cognitive impairment may accompany stroke, we investigated in the present study whether treatment with MSF could produce beneficial effects in adult rats subjected to an experimental stroke model. Sprague-Dawley rats received transient 60 min intraluminal occlusion of the rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Second, decreased ACh content and corresponding impairments in learning and memory were found in rats with 4-vessel occlusion [15] . Third, ChAT immunostaining was shown to be decreased in rats with transient occlusion of the middle cerebral artery (MCAO) [16][17][18] . Fourth, rats with multiple small embolizations have been shown to produce multiple infarctions and exhibit decreases in cholinergic markers [19] .…”
Section: Cholinergic Deficiency In Vad Animal Models and Vad Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, decreased ACh content and corresponding impairments in learning and memory were found in rats with 4-vessel occlusion [15] . Third, ChAT immunostaining was shown to be decreased in rats with transient occlusion of the middle cerebral artery (MCAO) [16][17][18] . Fourth, rats with multiple small embolizations have been shown to produce multiple infarctions and exhibit decreases in cholinergic markers [19] .…”
Section: Cholinergic Deficiency In Vad Animal Models and Vad Patientsmentioning
confidence: 99%
“…In fact, the effects of these AChE inhibitors have already been well evaluated in the treatment of VaD. Although the results were inconsistent, application of AChE inhibitors showed promising benefits in ameliorating the learning and memory impairments as well as other deficits found in VaD patients and VaD animal models [6,16,[70][71][72][73] .…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that ChAT levels are notably decreased in a number of pathologies, such as Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis, schizophrenia and sudden infant death syndrome (Oda, 1999), but an increase of ChAT activity is not a consistent change connected to a particular physiologic state or pathology, although some reports mention that enhanced acetylcholine synthesis accompanies learning (Oh et al, 1996;Park et al, 1992). However it has been reported that MSF treatment -after experimentally induced stroke in rats-showed more intense staining of septal ChAT-immunoreactive neurons correlating with a better response in learning and memory tasks (Borlongan, Sumaya and Moss, 2005). These findings suggest that MSF, probably by cholinergic system's enhancement, lessened stroke-induced deficit in learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Deleterious infarctions of the middle cerebral artery (MCA) are at risk of developing massive edema because of the necrosis of cells located in the primary zone (Borlongan et al, 2005). The most effective drug, tissue plasminogen activator, the only Food and Drug Administration-approved thrombolytic drug used in ischemia, is widely employed in clinic.…”
Section: Introductionmentioning
confidence: 99%